Src kinase phosphorylates Caspase-8 on Tyr380: a novel mechanism of apoptosis suppression - Cursi, Silvia; Rufini, Alessandra; Stagni, Venturina; Condò, Ivano; Matafora, Vittoria; Bachi, Angela; Bonifazi, Antonio Paniccià; Coppola, Luigi; Superti-Furga, Giulio; Testi, Roberto; Barilà, Daniela (The EMBO journal, 2006)
We identified Caspase‐8 as a new substrate for Src kinase. Phosphorylation occurs on Tyr380, situated in the linker region between the large and the small subunits of human Procaspase‐8, and results in downregulation of Caspase‐8 proapoptotic function. Src activation triggers Caspase‐8 phosphorylation on Tyr380 and impairs Fas‐induced apoptosis. Accordingly, Src failed to protect Caspase‐8‐defective human cells in which a Caspase‐8‐Y380F mutant is expressed from Fas‐induced cell death. Remarkably, Src activation upon EGF‐receptor stimulation triggers endogenous Caspase‐8 phosphorylation and prevents Fas‐induced apoptosis. Tyr380 is phosphorylated also in human colon cancers where Src is aberrantly activated. These data provide the first evidence for a direct role of tyrosine phosphorylation in the control of caspases and reveal a new mechanism through which tyrosine kinases inhibit apoptosis and participate in tumor progression.